Leprosy stigma post elimination era-a systematic review - Gary Goh Chun Chao; Sheila Miriam Mujin; Priya Dharishini Kunasagran; Mohd Hafizuddin Ahmad; Khairul Nizam Anwar; Azizan Omar; Richard Avoi; Syed Sharizman Syed Abdul Rahim; Fredie Robinson; Azman Atil (Universiti Putra Malaysia, 2024)
Introduction: Leprosy, an ancient communicable disease, was declared eliminated as a public health programme globally in 2000. However, despite the significant reductions in leprosy cases, and the achievement of post-elimination status in many regions, stigmatisation of leprosy persists despite commendable efforts to address it, which could hamper the road towards ‘Zero Leprosy’. Hence, the purpose of this review was to investigate and improve the understanding of leprosy stigma and to develop interventions that can effectively reduce the prevalence of leprosy. Materials and methods: To identify relevant articles, we employed the SPIDER framework (Sample, Phenomenon of Interest, Design, Evaluation, and Research type). Our search was conducted on Scopus, PubMed, ScienceDirect, BMJ, and SpringerLink Databases following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search strategy incorporated Boolean operators “AND” and “OR”, connecting keywords leprosy, stigma, and post-elimination. Results: The review included five articles and used Joanna Briggs Institute (JBI) Critical Appraisal Tool to appraise. Most articles narrated the three main domains: causes, phenomenon, and impact. The three main attributes discussed were misconception of disease (60%), external stigma (60%) and social impact (100%) as the leading cause of stigma. Conclusion: This systematic review still finds and adds a wider aspect to leprosy stigma in the post-elimination era, which could impose severe repercussions in effective disease control programmes towards the goal of ‘Zero Leprosy’. It recommends targeted actions aimed at individuals, communities, and institutions to counter stigma, including education, empowering those affected, involving communities, sensitising healthcare workers, and enacting supportive laws.